Acoustics of Materials - El Abiddine Fellah, Zine; Ogam, Erick (IntechOpen, 2019)
This book deals with acoustic wave interaction with different materials, such as porous materials, crystals, biological tissues, nanofibers, etc. Physical phenomena and mathematical models are described, numerical simulations and theoretical predictions are compared to experimental data, and the results are discussed by evoking new trends and perspectives. Several approaches and applications are developed, including non-linear elasticity, propagation, diffusion, soundscape, environmental acoustics, mechanotransduction, infrasound, acoustic beam, microwave sensors, and insulation. The book is composed of three sections: Control of Sound - Absorbing Materials for Damping of Sound, Sound Propagation in Complex/Porous materials and Nondestructive Testing (NDT), Non Linearity, Leakage.